Pegaruh PhET Terhadap Literasi Sains Materi IPA Kelas VI SDN Socah 3 - Pramesti, Adela Hana; Rahmawati, Ika Dian; Wulandari, Rika (Yayasan Arrahman Nahdlatul Wathan, 2024)
This study was prompted by the inadequate grasp of students' comprehension in various dimensions of science, encompassing content, context, processes, and scientific attitudes, alongside the limited availability of laboratory resources within the school setting. The primary objective was to discern variations in the attainment of scientific literacy scores among sixth-grade students studying Natural Sciences at UPTD SDN Socah 3. The research enlisted 23 sixth-grade students from UPTD SDN Socah 3 as participants. Employing a pre-experimental approach, the study utilized the One Group Pretest Posttest Design. Upon analyzing the data using paired sample t-test at a significance level of 0.05, the null hypothesis (Ho) was rejected, and the alternative hypothesis (Ha) was accepted. The noteworthy disparity between pre-test and post-test outcomes was substantiated by the computed t-value (13.445), surpassing the critical t-table value (2.074). Consequently, it can be deduced that employing PhET Simulation media yielded a considerable impact in augmenting students' scientific literacy skills pertaining to the comprehension of Natural Science material among sixth-grade students at SDN Socah 3.